1997
DOI: 10.1152/ajpregu.1997.272.1.r34
|View full text |Cite
|
Sign up to set email alerts
|

Contractile properties of rat, rhesus monkey, and human type I muscle fibers

Abstract: It is well known that skeletal muscle intrinsic maximal shortening velocity is inversely related to species body mass. However, there is uncertainty regarding the relationship between the contractile properties of muscle fibers obtained from commonly studied laboratory animals and those obtained from humans. In this study we determined the contractile properties of single chemically skinned fibers prepared from rat, rhesus monkey, and human soleus and gastrocnemius muscle samples under identical experimental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
48
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 0 publications
15
48
1
Order By: Relevance
“…A few studies have isolated single fibres of specific fibre types, from the same muscle, in a large body mass range of mammalian species, to subsequently determine scaling relationships within the study. Similar scaling exponents to those reported by Medler for maximum shortening velocity have been found for type I muscle fibres [(M b -0.11 (Widrick et al, 1997) and M b -0.13 (Seow and Ford, 1991)]. However, these mammalian muscle scaling exponents have been determined using force-velocity studies (isotonic) that rely on curve-fitting techniques to estimate maximal shortening velocity (Marsh and Bennett, 1986), which they are prone to underestimate (Claflin and Faulkner, 1985;Widrick et al, 1997;James et al, 1998).…”
Section: Scaling Of Muscle Mechanicssupporting
confidence: 86%
See 2 more Smart Citations
“…A few studies have isolated single fibres of specific fibre types, from the same muscle, in a large body mass range of mammalian species, to subsequently determine scaling relationships within the study. Similar scaling exponents to those reported by Medler for maximum shortening velocity have been found for type I muscle fibres [(M b -0.11 (Widrick et al, 1997) and M b -0.13 (Seow and Ford, 1991)]. However, these mammalian muscle scaling exponents have been determined using force-velocity studies (isotonic) that rely on curve-fitting techniques to estimate maximal shortening velocity (Marsh and Bennett, 1986), which they are prone to underestimate (Claflin and Faulkner, 1985;Widrick et al, 1997;James et al, 1998).…”
Section: Scaling Of Muscle Mechanicssupporting
confidence: 86%
“…Similar scaling exponents to those reported by Medler for maximum shortening velocity have been found for type I muscle fibres [(M b -0.11 (Widrick et al, 1997) and M b -0.13 (Seow and Ford, 1991)]. However, these mammalian muscle scaling exponents have been determined using force-velocity studies (isotonic) that rely on curve-fitting techniques to estimate maximal shortening velocity (Marsh and Bennett, 1986), which they are prone to underestimate (Claflin and Faulkner, 1985;Widrick et al, 1997;James et al, 1998). Studies using the slack test, which directly measures unloaded shortening velocity, have demonstrated larger scaling exponents (-0.18 to -0.21) in slow fibres than have been found using force-velocity studies (Table·1).…”
Section: Scaling Of Muscle Mechanicssupporting
confidence: 86%
See 1 more Smart Citation
“…A previous study found that the maximal shortening velocity of single muscle fibres decreased with increased body mass (M b ), from rat to rabbit to horse, scaling M b −0.18 in slow fibres and M b −0.07 in fast glycolytic fibres (Rome et al, 1990). Various scaling exponents have been found in other more recent studies comparing single fibres of the same fibre type between various mammalian species (Seow and Ford, 1991;Widrick et al, 1997;Pellegrino et al, 2003;Marx et al, 2006), with much of the variation in slope thought to be due to the species included in the study (Marx et al, 2006). A comprehensive review of published data demonstrated that maximal shortening velocity decreased with increased body mass, scaling across species M b −0.25 , whereas maximal isometric stress showed no significant relationship with body mass (Medler, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…A handful of studies of the contractile properties and biochemical composition of human single muscle ®ber have been published (Fitts et al, 1989;Larsson & Moss, 1993;Harridge et al, 1995;Lankford et al, 1995;Larsson et al, 1995Larsson et al, , 1996Larsson & Frontera, 1997;Widrick et al, 1996Widrick et al, , 1997Galler et al, 1997). However, as noted above, the cellular mechanisms underlying muscle weakness and atrophy in aging humans have not been elucidated.…”
Section: Mechanisms Underlying Sarcopeniamentioning
confidence: 99%